Impact of Life Experiences on Cognitive Development - Thorndike, Robert M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
The kinds of life events that may affect cognitive development were explored for 777 students, mostly freshmen, enrolled in introductory social science courses at Western Washington University Bellingham (Washington). Cognitive functioning was assessed using the Measure of Epistemological Reflection (MER) of M. B. Taylor (1983). Students also completed a Life Events Questionnaire concerning events in their recent past. Seventy-five of the freshmen were retested after 1 year. Several factor analyses explored the structure of the MER. Significant life events were found to be associated with a higher level of cognitive functioning. The most pervasive was the personal experience of intense inner insight. Other themes that were seen with some consistency were: (1) experienced divorce, separation, or the end of a serious love relationship; (2) experienced major change in church activity; (3) experienced sexual difficulties; and (4) independently made an important life decision. Scores on the MER showed only modest positive correlations, suggesting that the total score should be viewed with caution as an index of cognitive development. This finding was supported by the factor analyses, which indicated more than one factor, suggesting that cognitive development might be better described with two scores. Five data tables and two figures illustrate the study. (SLD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Development; College Freshmen; Epistemology; Essay Tests; Factor Analysis; Higher Education; Individual Development; Life Events; Psychometrics; Student Experience; Test Reliability; Undergraduate Students; Measure of Epistemological Reflection; Reports, Research